Evaluasi Mutu Pelayanan Kesehatan terhadap Kepuasan Pasien di Instalasi Rawat Inap RS Imelda Pekerja Indonesia Medan - Tasya Estu Hidayana; Asriwati Asriwati; Nuraini Nuraini (Lembaga Pengembangan Kinerja Dosen, 2024)
The quality of health services is one of the important factors in the utilization of health services. Assessment of the quality of good health services is not limited to physical healing of the disease, but also to the attitude, knowledge and skills of officers in providing services, communication, information, courtesy, punctuality, responsiveness and the availability of facilities and physical environment. The research design used in this study was qualitative with in-depth interview techniques to key informants who were used as research objects totaling 1 (one) person, main informants 2 (two) people and supporters in this study totaling 3 (three) people with the characteristics as mentioned above, the total informants were 6 people. The results of the study all patients were satisfied with the physical evidence service (Tangible) about the cleanliness of the room in preventing and controlling infections. Some patients were satisfied with the responsiveness service regarding the collaboration of doctors, nurses and pharmacists in responding quickly to patient complaints. Some patients were satisfied with the reliability service regarding patient admission procedures, examination services, treatment and care. The conclusion is that there is an influence between service quality (Reliability, Responsiveness, Assurance, Empathy, Physical Evidence) on patient satisfaction at the inpatient installation of the Imelda Buruh Indonesia Hospital, Medan.